Sequential multiple-target chemosensor: Co2+, Cu2+, PPi, and HSˉ discrimination by a bis(half-salamo)-type probe. (9th February 2022) - Liu, Guo-Hua; Li, Mei; Li, Li-Li; Bian, Ruo-Nan; Dong, Wen-Kui
Abstract: A bis(half-salamo)-type chemosensor LPBHS based on phenanthroline, which can identify multiple targets continuously, was synthesized. The chemosensor LPBHS utilizes the N3 O cavities to combine with metal cations, and further identify the anions after the complexes have been formed. The chemosensor LPBHS has an O -phenanthroline unit with excellent luminescence, so that the strong fluorescence of the chemosensor LPBHS can be observed under 365 nm UV light. The quenching of luminescence occurs after the introduction of Cu 2+ and Co 2+ into the chemosensor LPBHS, which can be identified in natural light by observing the change in color of the solution with the naked eye. The LPBHS -Cu 2+ complex further recognizes HSˉ and PPi (pyrophosphoric acid), and strong luminescence are also observed under UV light after the addition of HSˉ and PPi to LPBHS -Cu 2+ . HSˉ and PPi can also be identified by the change in color of the solution under natural light with the naked eye. Using the strong fluorescence emission of LPBHS, a test strip was developed to detect Cu 2+ and Co 2+ rapidly, and the quenching of fluorescence was clearly observed under UV light. HSˉ and PPi can be further identified by the phenomenon of fluorescence recovery after Cu 2+ detection on the test strip. Graphical Abstract: UF0001